The prevalence of cancer in patients with multiple sclerosis (MS) who received rituximab: a systematic review and meta-analysis - O. Mirmosayyeb; V. Shaygannejad; N. Ebrahimi; H. Ghoshouni; M. Ghajarzadeh (Neurología (English Edition))
Objective: To estimate the pooled prevalence of cancer in patients with multiple sclerosis (MS) cases who were under treatment with rituximab. Methods: We searched PubMed, Scopus, EMBASE, Web of Science, and google scholar along with gray literature up to April 2021.The search strategy included the MeSH and text words as ((“CD20 Antibody” AND Rituximab) OR “Rituximab CD20 Antibody” OR Mabthera OR “IDEC-C2B8 Antibody” OR “IDEC C2B8 Antibody” OR IDEC-C2B8 OR “IDEC C2B8” OR GP2013 OR Rituxan OR rituximab) AND ((Sclerosis AND multiple) OR (sclerosis AND disseminated) OR ''disseminated sclerosis'' OR ''multiple sclerosis'' OR ''acute fulminating''). Results: The literature search revealed 3577 articles, after deleting duplicates 2066 remained. For the meta-analysis, 22 studies were included. Totally, 15599 patients were enrolled while 133 cancers were detected.The pooled prevalence of cancer in MS patients under treatment with rituximab is 1in 100,000 (I2 = 99.9%, p < 0.001). Conclusion: The results of this systematic review and meta-analysis show that the pooled prevalence of cancer in MS patients who received rituximab is 1 in 100,000 cases. Resumen: Objetivo: estimar la prevalencia combinada de cáncer en pacientes con casos de esclerosis múltiple (EM) que estaban en tratamiento con rituximab. Métodos: Realizamos búsquedas en PubMed, Scopus, EMBASE, Web of Science y Google Scholar junto con literatura gris hasta abril de 2021.La estrategia de búsqueda incluyó el MeSH y palabras de texto como ((''CD20 Antibody” AND Rituximab) OR “Rituximab CD20 Antibody” OR Mabthera OR “IDEC-C2B8 Antibody” OR “IDEC C2B8 Antibody” OR IDEC-C2B8 OR “IDEC C2B8” OR GP2013 O Rituxan O rituximab) Y ((Esclerosis Y múltiple) O (esclerosis Y diseminada) O ''esclerosis diseminada'' O ''esclerosis múltiple'' O ''fulminante aguda''). Resultados: La búsqueda bibliográfica reveló 3577 artículos, después de eliminar los duplicados quedaron 2066. Para el meta-análisis se incluyeron 22 estudios. En total, se inscribieron 15599 pacientes y se detectaron 133 cánceres. La prevalencia combinada de cáncer en pacientes con EM en tratamiento con rituximab es de 1 en 100.000 (I2 = 99,9 %, p < 0,001). Conclusión: Los resultados de esta revisión sistemática y meta-análisis muestran que la prevalencia combinada de cáncer en pacientes con EM que recibieron rituximab es de 1 en 100 000 casos.